Whole genome association analysis method for milk production traits of milk goats and application of whole genome association analysis method - SHI HENGBO; ZHANG KAI; FENG YIFANG; LIU JIANXIN (2023)
The invention belongs to the technical field of biology, and particularly discloses a whole genome association analysis method for milk production related traits of milk goats and application of the whole genome association analysis method. 330 ewes are randomly selected from two West Nong Saanen milk goat groups as experimental subjects for whole genome association analysis, related characters such as milk yield, milk components and breast phenotypes of the ewes are collected, blood samples are collected during the lactation period, genome DNA is extracted, the integrity, purity and concentration of the extracted genome DNA are detected, and the whole genome association analysis result is obtained. Finally, 298 qualified samples are re-sequenced, and then the seven indexes of the production-related traits of the Xinonsaenen milk goats are subjected to whole genome association analysis, and candidate genes are screened, so that theoretical support is provided for breeding of new varieties of high-quality milk